Perception of timbre in adult Cochlear implant users: Comparison of Iranian and Western musical instruments. (2nd January 2023) - Dasdar, Shayan; Nasresfahani, Azam; Kianfar, Nika; Zarandi, Masoud Motesadi; Mobedshahi, Farzad; Dabiri, Sasan; Kouhi, Ali
Abstract : Objectives: Cochlear implants (CI) have dramatically improved speech perception for patients with sensorineural hearing impairment. However, listening to music is a great challenge for them. This study examined the perception and appraisal of Iranian musical instruments comparing with similar Western instruments. Methods: Eleven adult CI users and 25 normal hearing (NH) individuals participated in this study. Musical stimuli of three commonly heard instrument pairs were prepared. Participants were asked to identify the instruments and rate their appraisal on a ten-point Likert scale (0 = dislike very much, 10 = like very much). Results: The instrument recognition rate was 40.6% among the CI users, and the mean appraisal score was 5.2 ± 2.7. NH listeners had none significant higher scores on both tasks with a recognition rate of 50.0% and the mean appraisal score of 6.9 ± 1.5. Iranian instruments were more recognized in both groups. Regarding their appraisal, the mean score for both types was almost equal in the NH group, while CI users more appraised Iranian instruments. Conclusion: In addition to better recognition of Iranian instruments, they were particularly better appraised in the CI group. Iranian instruments provide suitable musical pieces for CI recipients that can be considered in rehabilitation programs.